Empowering Women's Gardenia Flower Farming Groups by Raising the Potential of Ginger as a Processed Product - Amalina, Afnita Nur; Amrih, Dewi; Wibisana, Dharend Lingga (CV. Rayyan Dwi Bharata, 2025)
Land in rural areas can be used by women who are members of the Women's Farming Group as a means of producing food from agricultural activities. The Women's Farmers Group in Salakan Hamlet, Bangunjiwo, uses empty land to plant various types of horticultural plants such as eggplant, kale, spinach and chilies. The harvest was deemed to lack high selling value so the land was replaced with ginger cultivation. Ginger is a type of rhizome that is beneficial for human health so it can be processed into processed products ready for consumption. The service team strives to provide knowledge about processing ginger into products so that they can have high economic value. The education was carried out by explaining how to process ginger-based products such as candied ginger, instant ginger powder and ginger syrup. With this outreach, it is hoped that it will be able to equip the Salakan Gardenia Flower Farming Women's Group, Bangunjiwo in utilizing ginger into products that can be further produced for sale on the market so as to improve the welfare of the Women Farming Group.